The yield of rigid thoracoscopy in patients of undiagnosed exudative pleural effusion and comparison of pleural fluid and thoracoscopic findings between tuberculosis and malignancy - Hemant Kumar; Mohammad Arif; Sachin Kumar; Ved Prakash; Ajay Kumar Verma; Chanchal Rana; Saumya Shukla; R. A. S. Kushwaha (The Egyptian Journal of Bronchology, 2023)
Abstract Background Medical thoracoscopy is an essential tool in the evaluation of patients with pleural effusion who remain undiagnosed despite a thorough pleural fluid workup. Malignancy and tuberculosis are the two most common etiologies in such patients having completely different prognoses. Therefore, correct diagnosis is very important before starting treatment. This study was planned to study the yield of rigid thoracoscopy in such patients and to observe its associated complications. Furthermore, the difference in the profile of patients with malignancy and tuberculosis was also evaluated. Methods This was a single-center, exploratory, observational study done between 1st May 2021 to 31st December 2022. Patients with undiagnosed exudative pleural effusion defined as exudative pleural effusions as per Light’s criteria with negative Gene X pert and twice negative pleural fluid cytology for malignancy, underwent rigid thoracoscopy for confirmation of their diagnosis. Results A total of 160 patients, who fulfilled our inclusion criteria, were included in our study. Male to female ratio was 1.25:1, with a mean age of 57.3 years. The most common etiology observed was malignancy, seen in 120 out of 160 patients (75%), followed by tuberculosis, which was seen in 27 (17%) patients. A final diagnosis could be made in 158 patients, giving a diagnostic yield of 98.8%. 11.8% showed procedure-related complications without any mortality. Conclusion Rigid medical thoracoscopy has a very high diagnostic yield with few complications. A significant proportion of patients with straw-colored effusion can present with malignancy and vice versa. A few with ADA above 40 were diagnosed as having malignancy. Therefore, tissue-based biopsy with thoracoscopy can be easily performed to make a correct diagnosis with huge future implications in such patients.